A proposed QoS multicast routing framework for next-generation Wireless Mesh Network - Shittu, W. A.; Hassan Abdalla Hashim, Aisha; Anwar, Farhat; Al-Khateeb, Wajdi Fawzi Mohammed (IJCSNS, 2008)
Wireless Mesh Network (WMN) is the network architecture where nodes (e.g. APs, mesh routers) can communicate with one another via multi-hop routing or forwarding. This is possible because of its dynamic self- organization, self-configuration and self-correction characteristics, which enable flexible integration, quick deployment, easy maintenance, low-cost, reliable services and its capability for capacity enhancement, connectivity and throughput. Although the current standard defines Multicast as well as QoS as important issues for considerations on this type of network, how to merge these two, especially at the Network layer, has been left to the discretion of different service providers. This paper describes a framework for the QoS Multicast routing provisioning problems in the Next-Generation IEEE 802.11s. We assume a working QoS MAC layer protocol and propose a framework for ensuring QoS Multicasting at the Network layer.